2003
DOI: 10.1080/1042015022000037319
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics of Metal Nanoparticles in Glass Upon Irradiation-Assisted Processing

Abstract: Irradiation-assisted processing, i.e. ion, electron and laser irradiation, have been applied to fabricate metal=glass nanocomposites. The particle configurations are studied by transmission electron microscopy to get some insight into the rather complex formation mechanisms. Special attention is given to spheroidally shaped particles surrounded by smaller secondary particles observed upon ion beam mixing of silica=silver=silica layer compounds as well as irradiating femtosecond laser pulses on sodium silicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Previous reports show that in this laser fluence resputtering effects take place. 15,16 Barnes et al report the formation of hollow, shell-like particles due to resputtering in PLD, and the TEM observation in their study has similarities with the present study. 15 They report that, with increasing energy density, resputtering increases and the shapes of the NPs are also modified.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Previous reports show that in this laser fluence resputtering effects take place. 15,16 Barnes et al report the formation of hollow, shell-like particles due to resputtering in PLD, and the TEM observation in their study has similarities with the present study. 15 They report that, with increasing energy density, resputtering increases and the shapes of the NPs are also modified.…”
supporting
confidence: 88%
“…In some cases cavities are formed in the NPs, which are caused by local melting that result in mass redistribution. A similar explanation is given by Hofmeister, 13 who suggests that the melting can start from the inside of the NP, with the molten metal being ejected and leaving a hollow shell. The shape of the rings drastically changes from oval to circular when the depositions are made in Ar ambience ͑Fig.…”
supporting
confidence: 64%
“…These hollow NPs may form when a high-energy species (Al, O, Al + , O − , AlO) [24] or small Al x O 1−x clusters hit an Au NP, implants a short distance and stays trapped inside the Au NP. Alternatively, they may form because of local melting, which causes mass redistribution and the formation of cavities as proposed by Hofmeister et al [33]. This explanation proposed by Hofmeister assumes that ion irradiation can cause melting to start from the inside of the NP, with the molten metal being ejected and leaving a hollow shell.…”
Section: Discussionmentioning
confidence: 96%
“…Recent reports also show that the nature of the defects produced can be modified as a function of irradiation temperature [15]. The electron beam irradiation in Ag doped glass is also reported to create defects in the matrix being rather effective in forming particles of uniform size, shape and arrangement [16]. It is also demonstrated that proton-irradiation at room temperature in simplified glass compositions induces an increase of the glass polymerization and production of molecular oxygen dissolved in the glasses linked to the migration and segregation of alkaline ions [17][18][19].…”
Section: Introductionmentioning
confidence: 98%